2021
DOI: 10.3390/molecules26154492
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drug Load on the Printability and Solid-State Properties of 3D-Printed Naproxen-Based Amorphous Solid Dispersion

Abstract: Fused deposition modelling-based 3D printing of pharmaceutical products is facing challenges like brittleness and printability of the drug-loaded hot-melt extruded filament feedstock and stabilization of the solid-state form of the drug in the final product. The aim of this study was to investigate the influence of the drug load on printability and physical stability. The poor glass former naproxen (NAP) was hot-melt extruded with Kollidon® VA 64 at 10–30% w/w drug load. The extrudates (filaments) were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…However, the disadvantages of the FDM process include process parameter-dependent mechanical characteristics, poor surface finishing, and the fact that FDM printing materials are limited to thermoplastic polymers only [ 120 , 121 , 122 ]. However, numerous reports depicted its usage in dosage form development, such as that of Kissi et al [ 123 ], used an FDM-based 3D-printing technique to formulate naproxen (NPA)-containing ASDs using co-povidone. Based on the results of the DSC and XRPD analyses, it was discovered that the ASDs within the 3D-printed tablets (20–30% w / w NPA) were amorphous and were stable for a 23-week duration at room temperature and 37% relative humidity.…”
Section: Recent Advancements In the Manufacturing Of Asdsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the disadvantages of the FDM process include process parameter-dependent mechanical characteristics, poor surface finishing, and the fact that FDM printing materials are limited to thermoplastic polymers only [ 120 , 121 , 122 ]. However, numerous reports depicted its usage in dosage form development, such as that of Kissi et al [ 123 ], used an FDM-based 3D-printing technique to formulate naproxen (NPA)-containing ASDs using co-povidone. Based on the results of the DSC and XRPD analyses, it was discovered that the ASDs within the 3D-printed tablets (20–30% w / w NPA) were amorphous and were stable for a 23-week duration at room temperature and 37% relative humidity.…”
Section: Recent Advancements In the Manufacturing Of Asdsmentioning
confidence: 99%
“…In addition, XµCT has been employed as a quantitative approach to assess the drug-phase separation in patches that have been manufactured via HME and injection molding [ 165 ]. Kissi et al [ 123 ] prepared ASDs of Naproxen (NAP) with varying drug loads (10–30% w / w ) using 3D-printing technology. According to the results of the XµCT, the nozzle may not deposit material in all areas during the 3D-printing of tablets containing 20% w / w of drug, as specified in the design file, whereas only a few air voids were produced for the 30% w / w naproxen tablet, resulting in a denser structure, as observed in Figure 7 .…”
Section: Advances In Characterization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Kissi et al, HME-extruded filaments containing naproxen were discovered to be amorphous and by increasing the API ratio from 0-10% to 10-20%, the filament brittleness was reduced and printability improved without a compromise on ASD stability. This was due to the plasticizing effect imparted to the filament by the API [68]. In another study, Tan et al also showed that the configuration of the API in the filament and FDM-printed tablets remained amorphous and the polymeric solvent controls the ductility and flexibility of the formed filament, which, in turn, affects the efficiency of printing using FDM [69].…”
Section: Fdm 3d Printing and Amorphous Solid Dispersions (Asds)mentioning
confidence: 99%
“…Because 3DP in the pharmaceutical industry is still in its infancy, it may be difficult to scale up manufacturing to fulfil the demand for personalised medications at a large scale [100].…”
Section: Scalabilitymentioning
confidence: 99%